Divine Viewpoint of Rabindranath Tagore Development - Radheshyam Ilame, Dr. Veena (International Journal of Humanities and Education Development (IJHED), 2020)
The research paper deals with the Divine viewpoint of Rabindranath Tagore who was Vaishainavite poet, Novelist, story writer, and thinker and philosopher, a versatile personality. Humanistic view saw its full development after the advent of Renaissance in the European nations, and all faiths somewhere propounded the notion of fraternity, equity and liberty, and most of the people still believe that Tagore’s spiritual poetry as specified in the Gitanjali deals with Divine Element and mysticism demonstrating co-relationship between humanity, Divinity and the Universe, and Tagore’s humanistic view is closely associated with his spiritualism, nevertheless, it brings humanity close to Divinity. God loves to see in me not his servant but himself who serves all. According to Tagore salvation is not complete absorption into God but absolute dedication to humanity through love, service and joy.